1991
DOI: 10.1073/pnas.88.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma in transgenic mice.

Abstract: Ocular and cutaneous melanomas arose in new inbred lines of transgenic mice having an integrated recombinant gene comprised of the tyrosinase promoter, expressed in pigment cells, and the simian virus 40 early-region transforming sequences. The tumors were hypomelanotic and were histopathologically similar to corresponding human melanomas. Eye melanomas often originated at a young age, chiefly from the retinal pigment epithelium, also from the choroid, and rarely from the ciliary body. The eye tumors grew aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 20 publications
2
92
0
Order By: Relevance
“…Moreover, HMD2 amplification (encodes human ortholog of MDM2) occurs in only 3%-5% of human melanomas (Muthusamy et al 2006), raising questions as to the pathogenetic relevance of the p53 pathway in melanoma. On the other hand, support for a role for p53 has been suggested by Mintz and colleagues, who showed that SV40 T antigen (which inactivates both RB and p53) generates a highly penetrant and aggressive melanoma phenotype (Bradl et al 1991). More direct evidence for a role of p53 in melanoma suppression derived from Tyr-RAS + ; Trp53 +/− mutant mice.…”
Section: Arf-mdm2-p53 Pathwaymentioning
confidence: 88%
“…Moreover, HMD2 amplification (encodes human ortholog of MDM2) occurs in only 3%-5% of human melanomas (Muthusamy et al 2006), raising questions as to the pathogenetic relevance of the p53 pathway in melanoma. On the other hand, support for a role for p53 has been suggested by Mintz and colleagues, who showed that SV40 T antigen (which inactivates both RB and p53) generates a highly penetrant and aggressive melanoma phenotype (Bradl et al 1991). More direct evidence for a role of p53 in melanoma suppression derived from Tyr-RAS + ; Trp53 +/− mutant mice.…”
Section: Arf-mdm2-p53 Pathwaymentioning
confidence: 88%
“…22 Few animals develop these tumors spontaneously, and the transgenic models of pigmented intraocular tumors [23][24][25][26] are complicated by histological features that indicate retinal pigment epithelial differentiation (uveal melanomas develop from melanocytes of the iris, ciliary body or choroid and not from the retinal pigment epithelium; retinal pigment epithelial neoplasms are rarely encountered in humans 27 ). Following the precedent of studying the histogenesis of primary cutaneous melanoma in animals following the application of 7,12-dimethylbenz[a]anthracene (DMBA), 28 -30 Folberg et al 22,31 attempted to induce primary uveal melanocytic lesions by the repeated application of this carcinogen to the rabbit sclera.…”
Section: The Microcirculation Of Uveal Nevimentioning
confidence: 99%
“…By using a recombinant gene comprised of the tyrosinase promoter and the simian virus 40 transforming segment, Bradl et al (1991) established transgenic mouse lines in which primary skin melanomas arose later and less frequently than ocular melanomas. By introducing the ret recombinant oncogene (Takahashi et al, 1985) fused to the mouse MT promoter-enhancer, we previously produced MT/ ret transgenic mouse lines with a mixed strain background (C57BL/6xBALB/c) (Iwamoto et al, 1991).…”
mentioning
confidence: 99%